Problematizing 'predatory publishing': A systematic review of factors shaping publishing motives, decisions, and experiences. Issue 2 (23rd August 2020) - Mills, D.; Inouye, K.
Abstract : This article systematically reviews recent empirical research on the factors shaping academics' knowledge about, and motivations to publish work in, so‐called 'predatory' journals. Growing scholarly evidence suggests that the concept of 'predatory' publishing' – used to describe deceptive journals exploiting vulnerable researchers – is inadequate for understanding the complex range of institutional and contextual factors that shape the publication decisions of individual academics. This review identifies relevant empirical studies on academics who have published in 'predatory' journals, and carries out a detailed comparison of 16 papers that meet the inclusion criteria. While most start from Beall's framing of 'predatory' publishing, their empirical findings move the debate beyond normative assumptions about academic vulnerability. They offer particular insights into the academic pressures on scholars at the periphery of a global research economy. This systematic review shows the value of a holistic approach to studying individual publishing decisions within specific institutional, economic and political contexts. Rather than assume that scholars publishing in 'questionable' journals are naïve, gullible or lacking in understanding, fine‐grained empirical research provides a more nuanced conceptualization of the pressures and incentives shaping their decisions. The review suggests areas for further research, especially in emerging research systems in the global South.